2015
DOI: 10.1038/ejhg.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

A SPRY2 mutation leading to MAPK/ERK pathway inhibition is associated with an autosomal dominant form of IgA nephropathy

Abstract: IgA nephropathy (IgAN) represents the most common primary glomerulonephritis worldwide with a prevalence of 25-50% among patients with primary glomerulopathies. In~5-10% of the patients the disease segregates with an autosomal dominant (AD) pattern. Association studies identified loci on chromosomes 1q32, 6p21, 8p23, 17p13, 22q12, whereas classical linkage studies on AD families identified loci on chromosomes 2q36, 4q26-31, 6q22, 17q12-22. We have studied a large Sicilian family where IgAN segregates with an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…& IgA disease. About 15% of all cases of IgA disease have another affected family member [80] and although GWAS analyses have identified chromosomal loci, relatively few genes have been identified [81].…”
Section: Biallelic and Digenic Mutations Affect The Clinical Phenotypmentioning
confidence: 99%
“…& IgA disease. About 15% of all cases of IgA disease have another affected family member [80] and although GWAS analyses have identified chromosomal loci, relatively few genes have been identified [81].…”
Section: Biallelic and Digenic Mutations Affect The Clinical Phenotypmentioning
confidence: 99%
“…They speculated that the IgAN disease status may be affected by a series of mutations that affect immune-related networks (25). Milillo et al identified the SPRY2 gene related to IgAN, which is part of the MAPK/ERK pathway (26). So, we hypothesized that variants in some pathways caused by TRPC6 mutations are risk factors for the development of immune-complex deposition nephropathy.…”
Section: Discussionmentioning
confidence: 93%
“…The increasing number of larger GWASs in different populations has unveiled numerous IgAN-associated loci, including complement factor H-related (CFHR) genes [49][50][51] , or those encoding defensing (DEFA) [47,52] , HLA [53] , sprouty RTK signaling antagonist 2 (SPRY2) [54] , vav guanine nucleotide exchange factor 3 (VAV3) [46] , core 1 synthase, glycoprotein-N-acetylgalactosamine 3-beta-galactosyltransferase 1 (C1GALT1) [55] , and tumor necrosis factor superfamily member 13 (TNFSF13) [56] .…”
Section: Iga Nephropathymentioning
confidence: 99%
“…They reported that the allelic frequencies of the variants within ST6GAL1 (encoding ST6 beta-galactoside alpha-2,6sialyltransferase 1), ACCS (encoding 1-aminocyclopropane-1-carboxylate synthase homolog), and DEFA correlated with geographical variations in IgAN prevalence. Milillo et al [54] reported that a SPRY2 mutation inhibited the mitogen-associated protein kinase/extracellular signal-related kinase pathway, which was associated with an autosomal dominant form of IgAN. Gale et al [55] reported that a common variation in C1GALT1 influenced galactose-deficient IgA1 levels in the population, which was independently associated with the risk of progressive IgAN.…”
Section: Iga Nephropathymentioning
confidence: 99%